(untitled) (Interdisciplinary Studies Journal, 2026)
The study analyzed the relationship between academic experiences and quality of life among Occupational Therapy students at the State University of Pará. The research provides an understanding that entering and remaining in higher education requires significant adaptations and can impact both academic performance and student well-being. The main objective was to analyze the academic experiences and quality-of-life perceptions of Occupational Therapy students, considering relevant sociodemographic aspects. This was a cross-sectional, descriptive, and quantitative study conducted with 122 regularly enrolled students, using the WHOQOL-BREF and the Revised Academic Experiences Questionnaire (QVA-r). The results showed a predominance of moderate adaptation among participants, with a positive highlight for the career dimension and weaknesses related to the psychological and environmental quality-of-life domains. A statistically significant association was observed between quality of life and variables such as sex, income, place of origin, and occupational activity, indicating that contextual factors directly influence student well-being. It is concluded that academic overload and the identified vulnerabilities reduce quality of life, reinforcing the need for integrated institutional policies, student assistance actions, and psychological support to promote retention and the integral development of students.